2022
DOI: 10.3390/su14159675
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating the Effects of COVID-19 and Vaccination on Employment Behaviour: A Panel Data Analysis Acrossthe World

Abstract: COVID-19 is a fast-invading virus that quickly invaded the human body and made no human activity immune to its infections. The purpose of this study is to simulate the effects of COVID-19 on employment behaviour and vaccination’s weight in the recovery process. Based on quarterly panel data from 43 nations from 2018 to 2020, we built an adaptive employment model. The major findings demonstrate that COVID-19 has negative and large net and second effects, with parameters of −7049 and −15,768 employees each quart… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 56 publications
0
2
0
Order By: Relevance
“…To prevent and control the transmission of the COVID-19, Chinese government have had to implement a series of lockdown policies, which had led to difficulties in rework, shutdown of work and production, which greatly influenced the demand of employment ( 26 , 27 ). Affected by the epidemic, global working hours reduced by 5.2% in the first quarter of 2020, and the effect was expanded in the second quarter, reaching 18.2%, then dropped to 7.2 and 4.6% in the third and fourth quarter, respectively ( 28 ). The COVID-19 pandemic has caused enormous disruptions in the U.S. labor market.…”
Section: The Impacts On the Employment Of College Graduates Caused By...mentioning
confidence: 99%
“…To prevent and control the transmission of the COVID-19, Chinese government have had to implement a series of lockdown policies, which had led to difficulties in rework, shutdown of work and production, which greatly influenced the demand of employment ( 26 , 27 ). Affected by the epidemic, global working hours reduced by 5.2% in the first quarter of 2020, and the effect was expanded in the second quarter, reaching 18.2%, then dropped to 7.2 and 4.6% in the third and fourth quarter, respectively ( 28 ). The COVID-19 pandemic has caused enormous disruptions in the U.S. labor market.…”
Section: The Impacts On the Employment Of College Graduates Caused By...mentioning
confidence: 99%
“…Regarding these difficulties, vaccination seemed to play a role in employment. Mosbah and Dharmapala [66], analyzing data from 43 nations between 2018 and 2020, found that while COVID-19 harmed workers, after vaccination and especially after the establishment of partial immunity, positive effects were cited on the workforce and employee behavior. However, the job retention support that was provided was beneficial for the Estonian labor market, because 20% of jobs were saved when they were supported by the program, also decreasing the rate of unemployment by 2-4 percentage points [67].…”
Section: Job Retentionmentioning
confidence: 99%